Synthesis of multilayered hexagonal boron nitride microcrystals as a potential hydrogen storage element - Ahmad, P. (Elsevier Ltd, 2017)
Top-down approach has been used to synthesize pure, highly crystalline, multilayered micron size crystals of hexagonal boron nitride (BNMCs) at the top of Silicon substrate at 800 °C by using bulk boron nitride powder as a precursor. The synthesized crystals have different interlayers spacing from left to right (0.33 nm, 0.37 nm and 0.35 nm) and at the center (~0.24 nm). The former spacing corresponds to d(002) spacing whereas the later corresponds to d(010) spacing in h-BN. The sharpness of the peaks in XRD, Raman and FTIR spectrums correspond to highly crystalline nature of BNMCs whereas the locations of the peaks verify the h-BN nature of BNMCs. The B-N bonded BNMCs with larger surface area can be an excellent choice as a hydrogen storage element. © 2017 Elsevier Ltd and Techna Group S.r.l.